Examining the Indian Metro Rail Construction Industry's EOT (Extension of Time) Claim Process and Including a Case Study (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2020)
A project is a series of tasks with a predetermined end date. Any action that is on the project's critical path that is delayed will affect the project's completion date and result in time overruns. One of the key determinants of the project's success is time overruns. It might be the result of force majeure, employer error, interface contractor error, or contractor error. Analyzing the reason for the delay is necessary, and if the contractor is not at fault, they are entitled to the extra time. India takes a distinct method while requesting EOT from FIDIC and other foreign agencies since contracts are structured in accordance with CPWD and military engineering services.